Programa Brasil Carinhoso: uma análise no contexto de reconfiguração da Política Social e no atendimento das demandas das mulheres-mães em São Luís/MA - França, Maria Veras (2017)
The BC is a federal government program aimed at early childhood, with the aim of stimulating the creation of day care centers and opening new places in existing day care centers for children aged 0-3 and thus reducing the inequality of access to education between the poor and the rich. It is part of the programs developed by the Social Assistance Policy in the context of reconfigurations of social policies under the impositions of neoliberal capital. The objective was to analyze this Program in São Luís-MA, in the current context of Social Assistance in relation to meeting the demands of women mothers and children from 0 to 6 years of age by daycare centers in the period from 2012 to 2015. It counted on the contribution (1 public and 2 community) located in the neighborhoods of Palmeira Village, Guardian Angel and Embratel Village, 12 mothers-women with children aged 0-6 enrolled in PBF-BC and 2 representatives of the Municipal Secretariat of Education of São Luís (SEMED) and 3 pedagogical directors/coordinators of the day care centers. The conception of day care that guided the study was public policy, social and universal right of urban and rural workers (and) and children up to 5 years of age to education, which has the duty of the State to guarantee it as a public good, free and of quality. This is a critical and qualitative study, which shows that daycare continues to be a "subpriority" of municipalities, and that the Program did not cover the historical demands, because parents still find it difficult to find places in public facilities, Which entails the transfer of responsibility of the municipality to private institutions, whether philanthropic or community. And these, in turn, also showed difficulties in receiving the encouragement of FUNDEB via BC. Situations that contradict BC's purposes and goals and, consequently, have not been able to change the quantitative and qualitative reality of day care centers in São Luís and the poorest families to whom the Program is intended.